ANALISIS PERSIAPAN MAHASISWA DALAM MENGIKUTI PERKULIAHAN MATA KULIAH GEOGRAFI REGIONAL SEMESTER III B PADA PRODI PENDIDIKAN GEOGRAFI TAHUN AJARAN 2022/2023 - Pamungkas, Bella Theo Tomi; Mundiarti, Vanida (Jurnal Geografi, 2022)
This research examines the preparation of students in exploring lectures in the Regional Geography course in semester III B and the influence between physical preparation and non-physical preparation on students' readiness to experience lectures. The benefits of this research are knowing the reflection of student lecture preparation and the situation and sharing data with students in preparing themselves for lectures. The population in this research are students of the Geography Learning Study Program of approximately 130 students. Sampling with stratified proportional random sampling technique as many as 47 students. This research uses research trials to test the validity of the instrument. There are 28 questions. will be experimented on 20 respondents, based on the results of the validity analysis, obtained rxy for each item is greater than r. the table at n = 20 is 0.444. And the results of the reliability analysis of each instrument have a reliability coefficient greater than rtable (0.444).The results of the research prove that there is no significant effect between physical preparation on the readiness of students of the Geography Learning Department to experience lectures. This matter can be seen from the results of the Partial Test obtained t. count for preparation. sport of- 0.346 with probability. 0.731 > 0.05 which means the hypothesis. rejected. 0, 005 & lt; 0.05, which means that there is a significant effect between the preparation of the lecture module on the readiness of the Geography Study Program students to explore lectures with an efficient rate of 18.5%. The total efficient number given between physical preparation, lecture module preparation on the analysis of student readiness for lectures is 18.8% and 81.2% is influenced by other factors outside the physical preparation aspect or preparation in the lecture module.